Surveillance Pattern of Cases of Type 2 Diabetes Mellitus in Bone Regency - Masriadi; Jusni; Marsuki (Pakistan Journal of Nutrition, 2017)
Background and Objective: The prevalence of diabetes mellitus among the world’s populations continues to increase yearly. This study aimed to analyze the surveillance of the case pattern of type 2 diabetes mellitus at 9 Local Government Clinics during the year 2016 in Bone Regency. Materials and Methods: This was an observational study using a cross-sectional analysis. The population of the study was patients with type 2 diabetes mellitus at 9 Local Government Clinics in Bone Regency from January-July, 2016. The sampling method used in this study was multistage sampling. Analysis of the data was conducted using SPSS software, the frequency and ArcView Geographical Information System (GIS) 9.1 software programs. Results: The results of the study revealed that the cases of type 2 diabetes mellitus among all respondents were more prevalent in the 45-54 age group (35.4%) and significantly higher in the female group than in the male group (68.6%). The highest number of visitations was found at the Watampone Local Government Clinic (42.6%) and the highest number of cases of type 2 diabetes mellitus was diagnosed in January (21.5%). Based on the spatial analysis using the GIS program, a low number of cases of type 2 diabetes was found at Awangpone, Paccing, Ulaweng, Cina, Kading and Sibulue, whereas a moderate number was found at Biru and Bajoe and the highest was found at the Local Government Clinic of Watampone. The number of cases of type 2 diabetes mellitus in the 45-54 age group was low at Awangpone, Paccing and Cina, moderate at Ulaweng, Watampone, Biru and Cina, low was also found at Paccing, Ulaweng, Bajoe, Kading and Sibulue. The female group had a higher rate of type 2 diabetes mellitus than the male group. In addition, the cases of type 2 diabetes mellitus were more numerous in urban areas than in rural areas and the most cases of type 2 diabetes mellitus were diagnosed in January due to the new year and short-term screening of sugar glucose. Conclusion: Based on the analysis results in this study, it was suggested that a screening approach and the Integrated Health Counseling Unit (Posbindu) be established at each working unit of the local government for the early detection of cases of type 2 diabetes mellitus. A high number of cases was not found at Bajoe, Kading and Sibulue and females have a higher risk of type 2 diabetes mellitus than males. The lowest number of cases was found at Awangpone.